2022
DOI: 10.1007/s11145-022-10309-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of communicative purpose and reading medium on pauses during different phases of the textualization process

Abstract: Multiple factors simultaneously interact during the writing process. The effect of these interacting factors must be considered if writing is studied as a dynamic and complex process that constantly changes. Based on that premise, the study aims to determine how the interaction between the reading medium and the communicative purpose of a writing task affects the pauses during different stages of the writing process. At the same time, it seeks to determine how this interaction is related to the writer's compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
3
8
0
Order By: Relevance
“…The study of Valenzuela and Castillo (2022) confirms the findings of previous studies that it is important to take into account timing or different phases when studying the writing process. Breetvelt et al (1994) and Rijlaarsdam and Van den Bergh (1996) showed that the moment at which certain actions occur and their variation across the writing process are essential when describing writing processes and their relation to the product (text quality).…”
Section: Temporal Dimension Of Activities During the Processsupporting
confidence: 87%
See 3 more Smart Citations
“…The study of Valenzuela and Castillo (2022) confirms the findings of previous studies that it is important to take into account timing or different phases when studying the writing process. Breetvelt et al (1994) and Rijlaarsdam and Van den Bergh (1996) showed that the moment at which certain actions occur and their variation across the writing process are essential when describing writing processes and their relation to the product (text quality).…”
Section: Temporal Dimension Of Activities During the Processsupporting
confidence: 87%
“…Three studies in this special issue investigate reading and writing processes of synthesis texts, sometimes in combination with different task types and learner groups. The studies deal with secondary school students (Barzilai et al, 2021) and university students (Castells et al, 2022;Valenzuela & Castillo, 2022). Barzilai et al (2021) and Castells et al (2022) start from a writing-to-learn perspective, that is, they investigate how writing can support content learning (from sources) or reading comprehension of source texts.…”
Section: Process Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, for instance, longer between-word and between-sentence pauses might indicate that the students gave more careful consideration to issues of sentence structure and vocabulary in the first phase of text simplification (Leijten et al, 2019a ). In contrast, the second phase was shorter and characterized by less frequent pauses, but with an overall longer average pause time, which seems to indicate that the students were mainly making limited revisions based on longer episodes of re-reading and re-checking their drafts, as was also observed in other studies (Perrin and Wildi, 2008 ; Xu and Xia, 2021 ; Valenzuela and Castillo, 2022 ).…”
Section: Discussionsupporting
confidence: 76%